Pornografia dziecięca - charakterystyka zjawiska - Krawulska-Ptaszyńska, Anna; Smelkowska-Zdziabek, Alicja (Wydział Prawa i Administracji UAM, 1997)
Child pornography is produced at the psychological expense of the photographed child. Child pornography can be defined as photographs, films, videotapes, magazines, and books that depict children of either gender in sexually explicit acts (alone, with other children, with adults, or with animals). The key word for persons interested in child pornography is the word collection, because all of them collect some depictions of children. Production of pornography is connected also with the phenomenon of child sex rings - groups consisting of one or more adult person (a lot of them are pedophiles) and several children making sex together or with other adult persons.
Child pornography